Composition of early planetary atmospheres: II. Coupled dust and chemical evolution in protoplanetary discs - Cridland, Alex J.; Pudritz, Ralph E.; Birnstiel, Tilman (Monthly notices of the Royal Astronomical Society, 2017)
We present the next step in a series of papers devoted to connecting the composition of the atmospheres of forming planets with the chemistry of their natal evolving protoplanetary discs. The model presented here computes the coupled chemical and dust evolution of the disc and the formation of three planets per disc model. Our three canonical planet traps produce a Jupiter near 1 AU, a Hot Jupiter and a Super-Earth. We study the dependence of the ﬁnal orbital radius, mass, and atmospheric chemistry of planets forming in disc models with initial disc masses that vary by 0.02 M above and below our ﬁducial model (Mdisc,0 = 0.1 M ). We compute C/O and C/N for the atmospheres formed in our three models and ﬁnd that C/Oplanet ∼ C/Odisc, which does not vary strongly between different planets formed in our model. The nitrogen content of atmospheres can vary in planets that grow in different disc models. These differences are related to the formation history of the planet, the time and location that the planet accretes its atmosphere, and are encoded in the bulk abundance of NH3. These results suggest that future observations of atmospheric NH3 and an estimation of the planetary C/O and C/N can inform the formation history of particular planetary systems.
Gesehen am 03.04.2018